Jonathan Edwards' Early Understanding of Religious Experience His New York Sermons, 1720-1723. - Stetina, Karin Spiecker (Lewiston : Edwin Mellen Press, 2011)
The significance of Scripture and piety had on Jonathan Edwards' theology has often been obscured by his innovative use of secular though and reformed theology in his public writings. This study focuses on his earliest sermons and personal writings, which stand [prior to his study of Locke and use of the technical term sense of the heart. In looking at Edwards' background, faith, and early sermons, this study presents an account of the emergence and expression of his early understanding of religious experience. True religion Edwards discovered, consists of the knowledge of God's glory, love an.
Stetina; Page 1; Page 2; Stetina PDF ISBN 0-7734-1221-2; Dedication; Contents; Foreword; Preface; Acknowledgements; Abbreviations; Note on the Text; Introduction; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Conclusion; Bibliography; Index; Scripture Index; Biography
Description based upon print version of record.
Keywords: Edwards, Jonathan, 1703-1758 -- Sermons; Experience (Religion).; Reformed Church -- Doctrines; United States -- Church history -- To 1775.; Religion; Edwards, Jonathan, -- 1703-1758 -- Sermons; Experience (Religion); Reformed Church -- Doctrines; United States -- Church history -- To 1775.; RELIGION / Christian Life / General; RELIGION / Christian Ministry / Preaching; Electronic books